2017
DOI: 10.1530/joe-17-0042
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the P2Y2 receptor regulates bone cell function by enhancing ATP release

Abstract: Bone cells constitutively release ATP into the extracellular environment where it acts locally via P2 receptors to regulate bone cell function. Whilst P2Y receptor stimulation regulates bone mineralisation, the functional effects of this receptor in osteoclasts remain unknown. This investigation used the P2Y receptor knockout ( ) mouse model to investigate the role of this receptor in bone. MicroCT analysis of mice demonstrated age-related increases in trabecular bone volume (≤48%), number (≤30%) and thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Deleting the mouse P2Y 2 receptor gene has produced conflicting results. Higher bone mineral content and BMD compared to wild‐type animals was seen by Orriss et al (2017), but Xing et al (2014) reported lower bone volume and strength. Consistent with the latter, overexpression of P2Y 2 receptors in female rats increased femoral length and strength of the femoral neck but had no effect on BMD (Ellegaard et al, 2017).…”
Section: P2y Receptors In the Musculoskeletal Systemmentioning
confidence: 89%
“…Deleting the mouse P2Y 2 receptor gene has produced conflicting results. Higher bone mineral content and BMD compared to wild‐type animals was seen by Orriss et al (2017), but Xing et al (2014) reported lower bone volume and strength. Consistent with the latter, overexpression of P2Y 2 receptors in female rats increased femoral length and strength of the femoral neck but had no effect on BMD (Ellegaard et al, 2017).…”
Section: P2y Receptors In the Musculoskeletal Systemmentioning
confidence: 89%
“…These actions are due to both P2 receptor mediated signalling and also direct hydrolysis by NPP1 to produce PP i (Orriss et al, ; Orriss, Key, et al, ; Orriss, Key, Hajjawi, & Arnett, ). Recently, we also demonstrated that activation of the P2Y 2 receptor exerts some of its effects on bone mineralization indirectly by promoting the release of ATP from osteoblasts (Orriss et al, ). In contrast to the potent actions of ATP and UTP, ADP and UDP do not influence bone mineralization (Orriss et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…The effect on bone mineralization is instead controversial. Mechanical forces promote ATP release followed by RUNX2 activation in a human osteoblastic cell line (Costessi et al, 2005) but low concentrations of ATP inhibit mineralization by binding P2Y2 receptor and mice lacking this receptor show an increased bone volume (Orriss et al, 2007;Orriss et al, 2017). Clopidogrel, an inhibitor of platelet aggregation used as a therapy for secondary prevention of the stroke, is an antagonist of P2Y12 receptor and in vitro was able to inhibit murine osteoblast proliferation and viability and to reduce osteoblasts' ability to form bone nodules.…”
Section: P2 Receptorsmentioning
confidence: 99%